0164 Early reporting incentives to reduce time between injury and claim: a multiple baseline interrupted time series analysis of two australian workers' compensation jurisdictions. (21st August 2017) - Lane, Tyler; Gray, Shannon; Hassani-Mahmooei, Behrooz; Collie, Alex
Abstract : Background: Early access to healthcare and work rehabilitation services provided by workers' compensation is associated with faster return to work and reduced claim costs. Incentivising employers to report claims early following injury may reduce time to service access and improve injured worker outcomes. We investigated the impact of legislated early reporting incentives on claim processing time in two Australian workers' compensation jurisdictions. Methods: A multiple baseline interrupted time series (ITS) design was used to evaluate incentive impact on claim processing time using Australian administrative workers' compensation data. We compared median days between injury and lodgement (lodgement time), lodgement and claim acceptance (decision time), and total processing time in South Australia (SA) and Tasmania (TAS). Results: Total time was not immediately affected by incentives, though there was a significant downward trend of one-third a day per month in both jurisdictions relative to the comparator. Lodgement time decreased significantly in both jurisdictions, though the magnitude of impacts differed. A concurrent increase in decision time was observed in TAS but not in SA. Conclusions: Our findings suggest that employer focused early reporting incentives may have long-term impacts on claim processing time. However, we also observed unanticipated effects such as increases to insurer decision making time, as well as differential impacts between jurisdictions despite identical policy intent. While co-occurring events such as other legislative changes limit causal inferences, ITS analyses provide a useful approach for investigating the impact of legislative change on policy relevant outcomes in workers' compensation systems.